2011
DOI: 10.1016/j.neuint.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

PKCβ-dependent phosphorylation of the glycine transporter 1

Abstract: The extracellular levels of the neurotransmitter glycine in the brain are tightly regulated by the glycine transporter 1 (GlyT1) and the clearance rate for glycine depends on its rate of transport and the levels of cell surface GlyT1. Over the years, it has been shown that PKC tightly regulates the activity of several neurotransmitter transporters. In the present work, by stably expressing three N-terminus GlyT1 isoforms in porcine aortic endothelial cells and assaying for [32P]-orthophosphate metabolic labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
4
17
1
Order By: Relevance
“…Several studies have demonstrated the role of PKC on endocytosis and posttranslational modifications of most transporters of the SLC6 family including GlyT1 [ 10 , 24 , 25 ]. For the dopamine transporter, we previously demonstrated that accelerated endocytosis triggered by PKC activation was a result of enhanced DAT ubiquitination [ 12 , 25 ], events further confirmed by other groups [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the role of PKC on endocytosis and posttranslational modifications of most transporters of the SLC6 family including GlyT1 [ 10 , 24 , 25 ]. For the dopamine transporter, we previously demonstrated that accelerated endocytosis triggered by PKC activation was a result of enhanced DAT ubiquitination [ 12 , 25 ], events further confirmed by other groups [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were incubated for 2 h with cycloheximide (50 μg/ml) to stop the delivery and synthesis of new proteins followed by treatment with DMSO (6 h) or 1 μM PMA for 6, 4, or 2 h. After incubations, the cells were washed and lysed as previously described. The cleared lysate was quickly mixed with loading dye and the proteins denatured by heating as previously described [ 10 , 11 , 21 ]. It is worth mentioning that glycine transporters expressed in cultured cells is not aggregated by heating, unlike the endogenous from tissue that aggregates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Vargas-Medrano et al (2011) showed that inhibition of PKCb abolished b-PMA-induced increases in DAT phosphorylation in PAE cells, suggesting that 904 this isoform is required for DAT phosphorylation upon PKC activation. Considering work by Chen et al (2013) discussed above seems to indicate that PKCb may act to elevate DAT surface levels, it is possible that phosphorylation of DAT by PKC activation actually supports DAT surface expression, despite the net decrease in surface levels upon nonspecific PKC activation by b-PMA.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 99%
“…GlyT1 protein is associated to glutamatergic synapses where its main function is to control the level of glycine (Zafra et al, 1995a;Zafra et al, 1995b;Cubelos et al, 2005;Jim enez et al, 2011;Vargas-Medrano et al, 2011). The inhibition of GlyT1 promotes an increase on glycine levels in synaptic terminals, which potentiates the NMDAR activation (Bergeron et al, 1998;Chen et al, 2003;Kinney et al, 2003;Lim et al, 2004;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%